FLOOR CRANE STRUCTURE DESIGN AS A TOOL FOR REPLACING BATTERY PACKS ON TMII TRAM MOVER - Anwar, Achmad Zainul; Asmara, I Putu Shindu; Purnomo, Dhika Aditya; Arif, Saiful (JISO : Journal of Industrial and Systems Optimization, 2024)
Tram mover is a train made by PT INKA (Persero) as one of the rides at TMII (Taman Mini Indonesia Indah) which uses batteries as an energy source. In the battery replacement process still uses manual lifting by requiring 4 workers. Each tram mover has 2 battery packs, requiring 4 lifts in each replacement process. There is no floor crane product on the market that can be used as a replacement tool in TMII station conditions. In this research, the design of tools for battery pack replacement is carried out. A floor crane with capacity, strength, and dimensions adapted to the conditions at TMII and the tram mover. The analysis process will use FEM (fenite element methods) approach using FEM based software. The validity of the simulation results is carried out on the value of the result of the safety factor, von misses stress, and deflection. The load used from weight of battery pack is 275 Kg. Arm static stress analysis obtained an actual minimum safety factor value of 2.004, maximum von mises stress of 123.9 MPa, and maximum total displacement of 5.206 mm. On the crutch obtained the actual minimum safety factor value of 2.518, stress von mises maximum of 98.59 MPa, and a maximum total displacement of 0.195 mm. on the chassis obtained the actual minimum safety factor value of 2.027, stress von mises maximum of 109.4 MPa, and a maximum total displacement of 0.2813 mm. Tram mover merupakan kereta yang dibuat oleh PT. INKA (Persero) sebagai salah satu wahana di TMII (Taman Mini Indonesia Indah) yang menggunakan baterai sebagai sumber energi. Pada proses penggantian battery pack masih menggunakan pengangkatan manual, dimana hal tersebut tidak efisien. Pada penelitian ini, dilakukan perancangan alat bantu untuk penggantian battery pack. Sebuah floor crane dengan kapasitas, kekuatan, dan dimensi yang disesuaikan dengan kondisi di TMII dan tram mover. Perancangan dan pengembangan produk menggunakan metode Ulrich yang memiliki output berupa desain produk terpilih berdasarkan kriteria pemilihan, kemudian dilakukan analisis kekuatan, analisis ergonomi, dan analisis biaya produksi. Analisis static stress lengan didapatkan nilai actual minimum safety factor sebesar 2.344, stress von mises maximum sebesar 105.9 MPa, dan displacement total maximum sebesar 12.97 mm pada lengan. Pada penopang didapatkan nilai actual minimum safety factor sebesar 2.518, stress von mises maximum sebesar 98.59 MPa, dan displacement total maximum sebesar 0.195 mm. pada chassis didapatkan nilai actual minimum safety factor sebesar 2.055, stress von mises maximum sebesar 120.8 MPa, dan displacement total maximum sebesar 0.3384 mm.